2006
DOI: 10.1001/archpsyc.63.7.795
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus and Amygdala Morphology in Attention-Deficit/Hyperactivity Disorder

Abstract: The enlarged hippocampus in children and adolescents with ADHD may represent a compensatory response to the presence of disturbances in the perception of time, temporal processing (eg, delay aversion), and stimulus seeking associated with ADHD. Disrupted connections between the amygdala and orbitofrontal cortex may contribute to behavioral disinhibition. Our findings suggest involvement of the limbic system in the pathophysiology of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
224
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 301 publications
(249 citation statements)
references
References 139 publications
(156 reference statements)
18
224
3
4
Order By: Relevance
“…Not only does our work complement several lines of evidence converging to hippocampal implication in patients with ADHD (Plessen et al, 2006;Posner et al, 2013Posner et al, , 2014Ho et al, 2015;Rivero et al, 2015), but also it extends these findings with respect to functional connectivity. In line with our asymmetry results, Posner and colleagues (Posner et al, 2014) found reduced volume and functional connectivity in the left hippocampus of ADHD children with respect to controls, and associated these modifications with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Not only does our work complement several lines of evidence converging to hippocampal implication in patients with ADHD (Plessen et al, 2006;Posner et al, 2013Posner et al, , 2014Ho et al, 2015;Rivero et al, 2015), but also it extends these findings with respect to functional connectivity. In line with our asymmetry results, Posner and colleagues (Posner et al, 2014) found reduced volume and functional connectivity in the left hippocampus of ADHD children with respect to controls, and associated these modifications with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our study clearly differs from previous studies both in the task and in the findings, pointing to hippocampal involvement in SR mechanisms involved in attention rather than to the WM processes implicated in those previous studies. The involvement of hippocampus as an attention controller is further supported by patients with posttraumatic stress disorder (PTSD) (Lindauer et al, 2006) and ADHD (Plessen et al, 2006). In summary, comparing the WMQ and WMN tasks of the present study, results demonstrate higher BOLD activity in the WMQ condition except in the bilateral anterior cerebellum, right posterior cerebellum, and left hippocampus.…”
Section: Comparing Wmq and Wmnsupporting
confidence: 70%
“…35 Moreover, genetic variants of PTPRD associate with bronchial asthma, 36 which is reported to occur at higher rates in children with ADHD, 37 and RLS patients have been shown to have increased use of asthma medications. 38 Studies of the PTPRD gene in mice show high expression in the hippocampus, the only brain region reported to be enlarged in ADHD, 39 along with involvement in spatial learning, long-term potentiation and axonal guidance of motor neurons. [40][41][42] Catecholaminergic neurotransmission is widely studied in ADHD and has yielded several candidate genes conferring a small amount of risk, suggesting a potential role for additional neurotransmitter systems.…”
Section: Resultsmentioning
confidence: 99%